2022
DOI: 10.5483/bmbrep.2022.55.5.035
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic approach with extracellular vesicles from stem cells for interstitial cystitis/bladder pain syndrome

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a debilitating chronic disorder characterized by suprapubic pain and urinary symptoms such as urgency, nocturia, and frequency. The prevalence of IC/BPS is increasing as diagnostic criteria become more comprehensive. Conventional pharmacotherapy against IC/BPS has shown suboptimal effects, and consequently, patients with end-stage IC/BPS are subjected to surgery. The novel treatment strategies should have two main functions, anti-inflammatory action and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 100 publications
0
4
0
1
Order By: Relevance
“…As a prominent symptom of IC/BPS, bladder pain seriously affects patients' ability to perform daily work and quality of life 35 . Due to the etiology and pathogenesis of IC/BPS remains elusive, traditional treatment methods do not guarantee a satisfactory therapeutic effect and even produce detrimental side effects 36 . TLR4 activation has been found to induce and maintain a high intensity pain state in a variety of chronic pain disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a prominent symptom of IC/BPS, bladder pain seriously affects patients' ability to perform daily work and quality of life 35 . Due to the etiology and pathogenesis of IC/BPS remains elusive, traditional treatment methods do not guarantee a satisfactory therapeutic effect and even produce detrimental side effects 36 . TLR4 activation has been found to induce and maintain a high intensity pain state in a variety of chronic pain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…35 Due to the etiology and pathogenesis of IC/BPS remains elusive, traditional treatment methods do not guarantee a satisfactory therapeutic effect and even produce detrimental side effects. 36 of the foot and dorsal root ganglion induces the release of pro-inflammatory factors, which is an important factor causing postoperative pain in patients. 37 It has been reported that the peripheral blood monocytes of IC/BPS patients can induce the release of pro-inflammatory cytokines IL-1β and IL-6 under the stimulation of TLR4 agonist Lipopolysaccharide (LPS) in vitro, which is closely related to the severity of pain in patients.…”
Section: Discussionmentioning
confidence: 99%
“…As it is well known indeed, in healthy conditions liver cell turnover is very slow, but at the same time, after 70% partial hepatectomy the liver is the only organ whose size returns to the original extent in about two weeks [20]. Despite this, in chronic and severe acute liver disease, this regenerative and replicative ability of the hepatic stem cells fails to regenerate the liver, as diffuse inflammation is present inducing increased production of matrix proteins, decreased matrix remodeling, progression to fibrosis, increase in the proportion of senescent hepatocytes (i.e., hepatocytes arrested at G1/S transition of the cell cycle) and hepatocyte death [21]. In this context, dogs primarily present with parenchymal pathologies such as hepatitis with an estimated frequency of up to 12% in the general canine population [21][22][23].…”
Section: Ivyspringmentioning
confidence: 99%
“…Despite this, in chronic and severe acute liver disease, this regenerative and replicative ability of the hepatic stem cells fails to regenerate the liver, as diffuse inflammation is present inducing increased production of matrix proteins, decreased matrix remodeling, progression to fibrosis, increase in the proportion of senescent hepatocytes (i.e., hepatocytes arrested at G1/S transition of the cell cycle) and hepatocyte death [21]. In this context, dogs primarily present with parenchymal pathologies such as hepatitis with an estimated frequency of up to 12% in the general canine population [21][22][23]. Considering this, in the present work we focused our attention on liver-inflamed diseases, to shift our previous study, on which we demonstrated that the use of mesenchymal stem cells in such pathology is a winning strategy [24], from a cell-based therapy to a cell-free therapy.…”
Section: Ivyspringmentioning
confidence: 99%
“…Considering the possible immune activation and tumorigenicity of stem cell therapy, MSC-derived extracellular vesicles (MSC-EVs) might resolve this problem. Further studies are needed to assess this potential therapeutic strategy [ 125 , 126 ].…”
Section: Treatment Of Ic/bpsmentioning
confidence: 99%